Microbial metabolite p-cresol inhibits gut hormone expression and regulates small intestinal transit in mice - Toft, Pernille Baumann; Vanslette, Amanda Marie; Trošt, Kajetan; Moritz, Thomas; Gillum, Matthew Paul; Bäckhed, Fredrik; Arora, Tulika (Frontiers in Endocrinology, 2023)
p-cresol is a metabolite produced by microbial metabolism of aromatic amino acid tyrosine. pcresol and its conjugated forms, p-cresyl sulfate and p-cresyl glucunoride are uremic toxins that correlates positively with chronic kidney disease and diabetes pathogenesis. However, how p-cresol affects gut hormones is unclear. Here, we expose immortalized GLUTag cells to increasing concentrations of p-cresol and found that p-cresol inhibited Gcg expression and reduced GLP-1 secretion in vitro. In mice, administration of p-cresol in the drinking water for two weeks reduced transcript levels of Gcg and other gut hormones in the colon; however, it did not affect either fasting or glucose induced plasma GLP-1 levels. Furthermore, it did not affect glucose tolerance, but promoted faster small intestinal transit in mice. Overall, our data suggests that microbial metabolite p-cresol suppresses transcript level of gut hormones and regulates small intestinal transit in mice.